Study profile choices in secondary education: searching for factors underlying the recommendations made by school guidance counsellors and tutors to vignette students - Wichgers, Inge J.M.; Korpershoek, Hanke; Warrens, Matthijs J.; Dijks, Monique A.; Bosker, Roel J. (British journal of guidance & counselling, 2023)
Dutch secondary education counsellors and tutors guide students in their study profile choices. Case studies were used to identify factors that characterise profile recommendations. In Case Study 1, vignette (fictitious) students asked for advice. Of the 12 participants, eight provided product advice (study profiles) and 12 provided process advice (important factors), mainly relating to students' interests. In Case Study 2, vignette students wanted to choose between a profile for which they had better marks, or one in which they were more interested. Of the 19 participants, 12 recommended study profiles. All participants provided process recommendations: these mainly involved interests, but also marks. In both case studies, recommendations were not characterised by students' SES, and a few were somewhat characterised by gender.